A high-throughput strategy for rapid synthesis and characterization of Ni-based superalloys - Zhao, Lei; Liu, Su-Ran; Jiang, Liang; Yang, Li-Xia; Zhu, Li-Long; Wang, Hui; Zhang, Wen-Yu; Huang, Zai-Wang; Deng, Yuan-Bin; Broeckmann, Christoph; Huang, Hai-Liang; Wang, Hai-Zhou (Rare metals, 2022)
This study developed a new high-throughput strategy, designated as hot-isostatic-pressing-based micro-synthesis approach (HIP-MSA), to optimize high-performance nickel-based superalloys in a rapid, efficient, and cost-effective manner. A specific honeycomb-array structure containing 106 discrete cells was designed and optimized using finite element analysis (FEA) and then applied to create a combinatorial library consisting of 106 Ni-based superalloys with various Co, Nb and Ta concentrations. By integration with high-throughput characterization tools, extensive composition and phase structure data were collected quickly and efficiently. In the superalloys with higher amounts of Nb and Ta, the detrimental η phase displaying needle-like morphology was observed, and its content (wt%) increased drastically with Ta and Nb contents increasing. However, the increase of Co addition in those alloys was confirmed to be surprisingly beneficial by significantly suppressing the formation of η phase that was induced by high Nb and Ta contents. The zero-phase-fraction (ZPF) line of η phase was established, which is critical to design superalloy chemistry for superior microstructural stability at high-temperature service conditions. Graphical abstract